Antioxidant nano-copper powder, preparation method thereof and nano-copper soldering paste
By adding soluble metal hydroxide and L-ascorbic acid to the copper salt solution, antioxidant nanocopper powder was prepared and used to prepare nanocopper solder paste, which solved the reliability problem of the third-generation semiconductor device packaging under low temperature conditions and achieved efficient and reliable sintering interconnection.
Patent Information
- Application Number
- CN202411468442.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The prior art is difficult to effectively package third-generation semiconductor devices under low temperature conditions, and the nano Cu powder has insufficient oxidation resistance, which affects the reliability of the packaging.
A preparation method is adopted to form a precursor solution and a reaction solution by adding soluble metal hydroxide and L-ascorbic acid to the copper salt solution, and then reacting with heating in a reducing alcohol to produce antioxidant nanocopper powder, which is used to prepare nanocopper solder paste.
It realizes efficient sintering and interconnection under low temperature conditions, improves the oxidation resistance and reliability of nano Cu powder, reduces sintering temperature and time, and meets the needs of third-generation semiconductor device packaging.
Smart Images

Figure CN119634742A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic packaging materials, and in particular to an anti-oxidation nano copper powder and a preparation method thereof, and a nano copper solder paste. Background Art
[0002] In the field of microelectronic packaging, the third-generation semiconductor materials represented by silicon carbide (SiC) and gallium nitride (GaN) have wide bandgap (>2.2eV), high breakdown voltage, good anti-radiation interference ability and chemical stability, and can have good conversion characteristics and working ability at high temperatures exceeding 300°C, so they are widely used in high-temperature and high-pressure working environments such as aerospace, smart grids, new energy vehicles, rail transportation, deep-sea exploration and nuclear reactions. However, such extremely harsh service conditions pose severe challenges to the packaging materials of devices. With the development trend of high-density interconnection and packaging miniaturization, it is required that the packaging materials must be able to achieve packaging interconnection at a lower temperature, while ensuring high service reliability under long-term high-temperature and high-pressure conditions.
[0003] Traditionally used packaging materials include tin-based solder and thermal conductive adhesive. However, the melting point of tin-based solder is generally low, and the melting point of the commonly used tin-silver-copper solder SAC305 is only 217°C; and because thermal conductive adhesive contains a large amount of resin components, its temperature bearing capacity is poor and its thermal conductivity is much lower than that of metal solder. These severely limit their application in third-generation semiconductor devices. In contrast, due to the nanoscale effect and high surface energy, nano metal powders show higher activity and diffusion rate at low temperatures, enabling them to achieve solid interconnection under low temperature conditions. After sintering, the theoretical service temperature and thermal conductivity of nano metal powders are much higher than those of tin-based solder, which has obvious advantages. Among them, compared with nano Ag powder, nano Cu powder is favored for its low cost, excellent electrical and thermal conductivity, and strong anti-electromobility. However, Cu itself has weak antioxidant capacity. The CuO generated after oxidation will seriously reduce the electrical and thermal conductivity and reliability of the interconnection joints, and the oxidation rate of nano-level Cu is further accelerated. Although current research focuses on introducing a high molecular weight organic coating, a core-shell structure or an acidic atmosphere to further improve the oxidation resistance of nano Cu powder, the antioxidant effect is not obvious and even affects the subsequent sintering quality. Therefore, a new synthesis method for simply and quickly preparing oxidation-resistant, uniformly sized and fine nano Cu powder is urgently needed. Summary of the invention
[0004] In view of the above technical problems, the present invention discloses an antioxidant nano copper powder and a preparation method thereof, and a nano copper solder paste. The obtained copper powder is antioxidant, has good stability in the air, reduces the risk of interface embrittlement, realizes low-temperature sintering interconnection of chips, and has high reliability of interconnection joints. It can be widely used in power electronic devices, especially third-generation semiconductor device packaging and other fields.
[0005] To this end, the technical solution adopted by the present invention is:
[0006] A method for preparing an antioxidant nano copper powder comprises the following steps:
[0007] Step S1, dissolving a copper salt in a solvent, adding a soluble metal hydroxide, and preparing a precursor solution; wherein the molar ratio of the soluble metal hydroxide to the copper salt is 0.5-2:1;
[0008] Step S2, dissolving L-ascorbic acid in a solvent, stirring at 40-80° C. for 10-20 min, waiting for the color to change to orange or reddish brown, and cooling to room temperature to obtain a reaction solution;
[0009] Step S3, mixing the precursor solution and the reaction solution to obtain a mixed solution, wherein the molar ratio of copper salt to L-ascorbic acid is 1:2-4; adding the mixed solution to a reducing alcohol, stirring evenly, heating to a reaction temperature of 155-195° C., and keeping the temperature for more than 15 minutes, and cooling to room temperature to obtain a product; wherein the use of a reducing alcohol can prevent the generated nano Cu from being oxidized to copper oxide or cuprous oxide again;
[0010] Step S4, washing, centrifuging and drying the product to obtain antioxidant nano copper powder;
[0011] The solvent in step S1 and step S2 is one or a mixture of two or more of 9-octadeceneamine, N,N-dimethyldodecyl tertiary amine, N,N-dimethyldodecylamine and N,N-diethyltrimethylsilylamine.
[0012] Among them, 9-octadeceneamine, N,N-dimethyldodecyl tertiary amine, N,N-dimethyldodecylamine, and N,N-diethyltrimethylsilylamine are long-chain alkylamines with dual functions of strong reducing agents and solvents. The long-chain alkyl part in the molecular structure of these long-chain organic amines can form a hydrophobic layer on the surface of nano Cu, hindering the agglomeration of nano Cu; at the same time, the amino part at the other end can make the nano Cu carry an electric charge and produce electrostatic repulsion, further reducing the agglomeration of particles, and finally ensuring the fine particle size of nano Cu and appropriate printing viscosity. Second, the long-chain alkylamine is liquid at room temperature. As a common reducing agent, compared with powdered L-ascorbic acid and other reducing agents, the liquid state is more conducive to the occurrence of redox reactions. At the same time, the reducing ion environment formed by the amino structure can further inhibit the oxidation of Cu. Third, from the perspective of sintering, although the above-mentioned long-chain alkylamine belongs to an oily coating layer, it can be quickly decomposed at a temperature of 150 to 160 ° C, promoting the rapid diffusion of subsequent nano Cu, and is very suitable for the preparation of nano Cu for sintering interconnection in the present invention.
[0013] In addition, the long-chain alkylamine used in the above technical solution is liquid at room temperature, and can directly play the dual role of stabilizer and solvent, preventing some of the reduced Cu atoms from being oxidized to copper oxide or cuprous oxide again, or the product directly generated during the reduction process contains a large amount of copper oxide, which effectively ensures the uniformity of fine Cu nanoparticles; at the same time, it also avoids the use of a large amount of solvent, and can still ensure a sufficient chemical reaction rate at low temperature or room temperature. In this way, when preparing the precursor solution, a uniform solution can be formed by stirring at room temperature, and the stirring operation at room temperature can form a more stable precursor solution to control the controlled release of Cu ions.
[0014] Third, from the perspective of sintering, the long-chain alkylamines selected in the technical solution of the present invention have certain volatility, and the initial boiling or decomposition temperature is 150-160°C, so that they gradually decompose on the surface of Cu nanoparticles during the heating stage of the sintering process, allowing the exposed Cu and Cu particle surfaces to contact each other, promoting the rapid diffusion of Cu atoms and improving the strength of the sintered joint.
[0015] By adopting this technical solution, adding hydroxide and other alkalis to the copper salt solution can provide abundant hydroxide ions in the solution state. A large amount of hydroxide ions react with Cu 2+ The formed precipitate phase inhibits the ionization and reduction process of Cu, and combines with long-chain organic amines with strong reducing agents and solvents to produce small-sized organic amine-coated nano Cu particles, so that the obtained nano Cu particles have good antioxidant properties.
[0016] In the above scheme, if soluble metal hydroxide is not added, the size of the obtained nano Cu particles is large (most of the particles are larger than 300nm). Too large particle size will not give full play to the high surface energy and rapid diffusion advantages of nano materials, so the required sintering temperature needs to be increased to achieve the same sintering density. Appropriate addition of soluble metal hydroxide can control the particle size and morphology.
[0017] Furthermore, the soluble metal hydroxide is sodium hydroxide or potassium hydroxide.
[0018] As a further improvement of the present invention, the copper salt is one of copper sulfate, copper chloride, copper nitrate, and copper acetate, or a mixture of two or more thereof. Further preferably, the copper salt is copper acetate.
[0019] As a further improvement of the present invention, in the precursor solution, the concentration of the copper salt is 0.1 to 1 mol / L, and the molar ratio of the soluble metal hydroxide to the copper salt is 1 to 2: 1. With this technical solution, a large amount of hydroxide ions can more significantly inhibit the ionization and reduction process of Cu ions, so that the organic amine has sufficient time to evenly coat the Cu atoms or clusters to produce fine-sized nano Cu particles. The obtained nano Cu particles are more uniform in size, which is conducive to sintering densification.
[0020] As a further improvement of the present invention, in the reaction solution, the concentration of L-ascorbic acid is 0.4-2 mol / L.
[0021] As a further improvement of the present invention, in step S3, the precursor solution and the reaction solution are mixed in equal volumes, and the volume ratio of the mixed solution to the reducing alcohol is 1:2 to 1:4.
[0022] As a further improvement of the present invention, the reducing alcohol is one or a mixture of two or more of ethylene glycol, thioethanol, isopropanol, hydroxypropanol, and tert-butanol.
[0023] As a further improvement of the present invention, in step S3, the heating rate is 20-40°C / min.
[0024] As a further improvement of the present invention, in step S3, the reaction time is 30 to 60 minutes. With this technical solution, the gradually accumulated energy reaches the nucleation work to promote the nucleation and subsequent growth of Cu, and the particle size is refined to about 80-100nm, and the distribution is uniform, which can give full play to the nanometer size effect and reduce the sintering temperature in subsequent use. When the reaction time is further increased to 120 minutes, the particle size increases instead. If the reaction time is too long to 150 minutes, the generated nanoparticles will adsorb each other under continuous thermal energy, and will agglomerate in large quantities during the cooling process, and the final Cu nanoparticle size is greater than 500nm or even micrometer level, which does not meet the low temperature sintering characteristics.
[0025] As a further improvement of the present invention, the reaction container in step S3 is glass or quartz. In addition to having high transparency and good optical properties like conventional glass, which makes it easy to observe the process and results of chemical reactions, the quartz glass container also has better high temperature resistance and chemical inertness. Due to the strong alkaline environment (addition of a large amount of soluble metal hydroxides, acetate ion ionization and reducing alcohol conditions) and the volatilization of organic vapor in this experiment, the quartz glass container can better withstand the strong alkaline environment, fully absorb the reaction heat, and withstand high gas pressure to ensure experimental safety.
[0026] As a further improvement of the present invention, in step S4, the solvent used for washing is methanol, dichloromethane or cyclohexane; further, the solvent used for washing is methanol and dichloromethane mixed in a volume ratio of 1: 2-3. The double bonds and amino groups in the long-chain organic amine structure are highly active functional groups. After reacting at the reaction temperature of step S3, oxidation of the double bonds and acylation of the amine will occur, and then become carboxylic acids, alcohols or amides (the polarity difference of these substances increases). Methanol itself has a large polarity, which is suitable for cleaning long carbon chains, especially alcohol structures. Dichloromethane itself has a relatively symmetrical structure and no separate hydrogen, has a lower polarity, and is very suitable for cleaning substances such as amides of the same symmetrical structure. Considering that the amine structure at the tail end has higher activity than the middle carbon-carbon double bond, its acylation reaction is bound to occur earlier and faster, and the amide content produced is higher. Therefore, when considering the relative content of methanol and dichloromethane, a higher volume ratio of dichloromethane is selected; and the volume ratio of methanol and dichloromethane is 1:3. After washing once, the residual organic matter around the particles is significantly reduced. After washing twice, the residual organic matter around the particles is almost gone, which has a better cleaning effect. In addition, these washing solvents are all highly volatile substances. After washing the residual organic amines, there is no need to worry about the introduction of other organic matter again, which will reduce the subsequent sintering quality.
[0027] As a further improvement of the present invention, in step S3, centrifugal washing is performed more than three times, and the centrifugal speed is 4000-6000 rpm.
[0028] As a further improvement of the present invention, the particle diameter of the antioxidant nano copper powder is 25-400 nm; the surface of the antioxidant nano copper powder is evenly covered with a dense organic amine coating layer.
[0029] The present invention also discloses an anti-oxidation nano copper powder, which is prepared by any of the above-mentioned methods for preparing anti-oxidation nano copper powders, wherein the surface of the anti-oxidation nano copper powder is covered with an organic amine coating layer. Furthermore, the particle diameter of the anti-oxidation nano copper powder is 25-400 nm.
[0030] The invention also discloses a nano copper solder paste, which is obtained by uniformly mixing the above-mentioned anti-oxidation nano copper powder with a solvent and a soldering flux; the mass ratio of the anti-oxidation nano copper powder, the solvent and the soldering flux is (7-9):(1-3):(0.02-0.06).
[0031] As a further improvement of the present invention, the solvent is pineol, and the soldering flux comprises ethyl cellulose and cellulose acetate. Adopting this technical scheme, on the one hand, pineol can effectively help active Cu powder to be evenly dispersed in solder paste, thereby improving the chemical stability of solder paste. This is crucial for ensuring the smooth progress of sintering process. On the other hand, the decomposition temperature of pineol is low and the residual carbon rate is low, which means that during the sintering process, the pineol in the solder paste can be fully volatilized, and the residue is less at the same time, which reduces the content of residual carbon in the sintered structure, and is conducive to improving the compactness and reliability of the sintered joint. The main components of the soldering flux are ethyl cellulose and cellulose acetate, and ethyl cellulose can adjust the appropriate viscosity to realize the uniform printing of solder paste on the chip; cellulose acetate can play the role of plasticizing and anti-oxidation, increase the viscosity of solder paste, and reduce the back of the chip or the surface tension of the substrate. In addition, the above two types of cellulose are used as adhesives and film-forming agents for the particles. They begin to decompose at about 200°C. They can adhere to the surface of nano-Cu, isolate water and oxygen in the air, and prevent nano-Cu from oxidizing and deteriorating during the heating process. At the same time, they can decompose during the heat preservation process without hindering the contact diffusion of Cu, which is beneficial to improving the density of Cu nanoparticles after sintering.
[0032] As a further improvement of the present invention, the stirring speed is 1800-2200 r / s, and the stirring time is 180-300 s.
[0033] As a further improvement of the present invention, the prepared solder paste is stored in a freezing environment of -5 to 0°C, and before soldering the upper and lower chips, the solder paste is thawed at room temperature for 1 to 2 hours before use.
[0034] The invention also discloses a low-temperature sintering interconnection method for components, which comprises applying the nano copper solder paste to the surface of the components to be welded, preheating, and then vacuum hot pressing and sintering.
[0035] As a further improvement of the present invention, the nano copper solder paste is evenly applied to the surface to be connected of the component by screen printing 2 to 3 times, the component is placed at the position to be connected after the first preheating, and after the second preheating, vacuum hot pressing sintering is used to achieve interconnection.
[0036] As a further improvement of the present invention, the material of the screen is nylon. Nylon screen has high strength and wear resistance, which enables it to withstand greater pressure and friction during printing. At the same time, good elastic tension and chemical stability further ensure the quality and durability of printing. In addition, the nylon screen has a uniform wire diameter and a smooth surface, which allows the solder paste to pass smoothly, reduces the phenomenon of blockage and ink hanging, and improves printing efficiency and quality.
[0037] As a further improvement of the present invention, the screen printing adopts a screen thickness of 20-50 μm and a mesh size of 200-300 meshes. The mesh size of the screen of 200-300 meshes is relatively small, which can better control the distribution of ink, make the edge of the printed pattern clearer, and achieve more delicate printing, which is suitable for small chip packaging structures.
[0038] As a further improvement of the present invention, before printing, the distance from the screen to the chip surface is set to 0.4-0.6 mm, the movement speed of the scraper is 0.5-1 cm / s, and the scraper angle is 5-15°.
[0039] With this technical solution, a distance of 0.4-0.6mm is used to ensure that the solder paste that leaks through the screen can have a certain thickness, and at the same time has an appropriate spreading effect and is evenly printed on the entire surface.
[0040] The scraper movement speed is 0.5 to 1 cm / s, which can drive the solder paste to leak into the mesh steadily and form a fine printing pattern. Due to the high viscosity of the nano Cu paste, when the scraper speed is high (over 1 cm / s), the solder paste quickly enters the mesh and has no time to leak through, and the filling of the solder paste becomes poor; at the same time, once the screen fluctuates at a high speed, it will cause uneven printing thickness. If the scraper speed is too low to below 0.5 cm / s, the printing efficiency is too low, which increases the time cost, and the solder paste accumulated on the screen will also cause uneven printing thickness.
[0041] As for the angle of the scraper, when the preset scraper angle is large, the deformation and wear of the scraper side edge are more serious, the squeezing force through the mesh is insufficient, and the solder paste is easily accumulated in front of the scraper side edge during the transfer process, which is prone to leakage. Especially for the nano Cu paste with higher viscosity, a larger scraper angle is more disadvantageous. In order to deal with this phenomenon, a smaller scraper angle (5-15°) is required to exert a greater downward squeezing force on the solder paste, approximate a straight line at the beginning of printing, and set the screen to the surface distance of 0.4-0.6mm before printing to increase the printing volume and leakage rate of the solder paste.
[0042] As a further improvement of the present invention, the scraper is made of polyurethane. The scraper is used to scrape the solder paste on the screen so that it is leaked on the chip or substrate to form an intermediate sintered layer with uniform thickness. The polyurethane scraper can maintain the elongation and resilience of the rubber under high hardness, and can reduce the damage to the scraper, screen and substrate surface. At the same time, due to its good chemical resistance, it can maintain the same appearance and performance after multiple screen printing, reducing the replacement frequency.
[0043] As a further improvement of the present invention, the first preheating temperature is 80-100°C, and the preheating time is 2-3 minutes; the second preheating temperature is 60-80°C, and the preheating time is 5-6 minutes. The purpose of the first preheating is to remove organic matter such as pineneol in the solder paste without destroying the organic amine coating layer on the surface of nano Cu. The preheating time should not be too long to prevent the nano Cu from agglomerating before sintering. The second preheating operation is immediately before the vacuum hot pressing sintering, and its purpose is to make the preheated nano Cu layer more easily reach the temperature required for sintering, improve the sintering efficiency, and reduce energy consumption.
[0044] Further preferably, the vacuum degree of the vacuum hot pressing sintering is less than 5×10 -2 MPa, pressure of 5-15MPa, and sintering temperature of 200-350℃. Further preferably, the sintering temperature is 200-350℃, and the sintering time is 15-40min; the shear strength of the interconnection joint after sintering can reach 48MPa. Vacuum conditions can inhibit the oxidation of Cu during the sintering process, and hot pressing conditions can increase the rapid diffusion and sintering densification between Cu particles. Since the nano Cu powder prepared by the technical solution of the present invention has only a thin organic amine coating layer on the surface, when the particle size is as low as 90nm, the strength of the interconnection joint obtained by sintering only under the sintering process of temperature 250℃, pressure 10MPa, and time 40min can reach 48MPa.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] First, the technical solution of the present invention improves the preparation method of the traditional nano Cu powder. By selecting suitable auxiliary agents and controlling the reaction conditions (reaction temperature, alkali concentration and reaction time, etc.) to regulate the long-chain amine coating effect, a uniform, dense and extremely thin small molecular weight organic amine coating layer is generated on the surface of the nano Cu powder, which significantly reduces the particle size of the nano Cu powder, inhibits the oxidation of Cu during the synthesis process, improves the stability of nano copper in the air, and reduces the risk of interface embrittlement in subsequent sintering. Moreover, the reaction in the technical solution is carried out in an atmospheric environment throughout the process, the reaction time is short (as low as 15min), and the operation is simple. Compared with the complex synthesis process of the prior art, it avoids the conditions of the device such as a high-temperature reactor and an inert gas environment, significantly reduces the manufacturing cost, and improves the production efficiency. At the same time, the solvents used in the reaction are all non-toxic or low-toxic reagents, which meet the production concepts of green chemistry and low-carbon manufacturing.
[0047] Second, the organic components in the nano solder paste in the technical solution of the present invention can volatilize and decompose under the set two preheating conditions, so that the nano Cu powder can fully contact, thereby promoting the sintering of the nano copper powder. In addition, the extremely thin small molecular weight organic amine coating layer on the surface of the nano Cu powder can be quickly decomposed at a sintering temperature of about 160°C, thereby promoting the rapid sintering and densification of Cu particles during the sintering process, further improving the reliability of the sintered joint.
[0048] Third, the technical solution of the present invention adopts a solder paste component and screen printing process that matches the nano Cu powder, and builds a corresponding sintering process window, giving full play to the characteristics of nano Cu powder such as low cost, resistance to electromigration, high surface energy and low temperature sintering, especially effectively reducing the sintering temperature and time, and obtaining interconnect joints with high printing accuracy (thickness 20μm), good antioxidant properties and high reliability interface, which meets the packaging needs of the third-generation semiconductor devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 These are scanning electron microscope / secondary electron mode (SEM / SE) images of Cu nanoparticles obtained at different reaction temperatures in Example 1 of the present invention, where (a) is 155°C, (b) is 175°C, and (c) is 195°C.
[0050] Figure 2 This is the X-ray diffraction spectrum of the Cu nanopowder in Example 1 of the present invention.
[0051] Figure 3 The transmission electron microscope bright field (TEM-BF) image of the Cu nanopowder obtained in Example 1 of the present invention and its energy dispersive spectrometer (EDS) surface scanning element distribution map, wherein: (a) TEM-BF image, (b) Cu element distribution map, (c) C element distribution map, and (d) O element distribution map.
[0052] Figure 4 These are SEM / SE images of Cu nanoparticles obtained at different molar ratios of sodium hydroxide to copper salt in Example 2 of the present invention, wherein (a) no sodium hydroxide is added, (b) 0.5:1, (c) 1:1, and (d) 2:1.
[0053] Figure 5 These are SEM / SE images of Cu nanoparticles obtained at different holding times in Example 3 of the present invention, where (a) is 15 min, (b) is 30 min, (c) is 60 min, and (d) is 120 min.
[0054] Figure 6 The strength variation curve of the sintered interconnect joints obtained in Examples 2 and 3 of the present invention in the shear test, wherein the peak value is the shear strength.
[0055] Figure 7 These are comparison photos of the solutions after the reaction of Example 1 of the present invention and Comparative Example 1. The reaction temperatures of a, b, and c are 155° C., 135° C., and 115° C., respectively.
[0056] Figure 8 This is a morphology photograph of the Cu nanoparticles obtained under the condition of heat preservation reaction for 150 minutes in Comparative Example 2 of the present invention.
[0057] Fig. 9 The following are photos comparing the cleaning effects of Examples 1 to 3 of the present invention and Comparative Example 3, wherein (a) water + ethanol (Comparative Example 3), (b) methanol + dichloromethane 1:2 (Comparative Example 3), and (c) methanol + dichloromethane 1:3 (Example 1).
[0058] Fig.10 This is a microstructure morphology diagram of the sintered joint of “chip-Cu nano solder paste layer-substrate” after sintering in comparative example 4 of the present invention. DETAILED DESCRIPTION
[0059] In order to better explain the present invention and facilitate understanding, the present invention is further elaborated in detail below with reference to the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the contents described.
[0060] A method for preparing an antioxidant nano copper powder comprises the following steps:
[0061] Step (a), dissolving copper salt in solvent A, and adding a certain amount of sodium hydroxide to prepare a precursor solution B;
[0062] Step (b), dissolving L-ascorbic acid in solvent A, and magnetically stirring at 40-80° C. for 10-20 min, until the color changes to orange or reddish brown, and cooling to room temperature to form a reaction solution C;
[0063] Step (c), mixing the precursor solution B and the reaction solution C, and then immediately adding the mixed solution into the reducing alcohol D, stirring evenly to obtain a reaction system;
[0064] Step (d), placing the reaction system in step (c) in a reaction vessel and heating it to a specified reaction temperature at a heating rate of 20 to 40° C. / min, and keeping the temperature for more than 15 minutes, and cooling to room temperature to obtain a dark red product E;
[0065] Step (e), washing, centrifuging and vacuum drying the product E to obtain nano copper powder, which is then sealed for standby use.
[0066] The concentration of copper salt in the precursor solution B is 0.1-1 mol / L, and the molar mass ratio of the concentration of sodium hydroxide to the copper salt is 0:1-2:1, preferably, the molar ratio of the concentration of sodium hydroxide to the copper salt is 1:1-2:1. The concentration of L-ascorbic acid in the reaction solution C is 0.4-2 mol / L; the precursor solution B and the reaction solution C are mixed in equal volumes, and the mixing ratio of the mixed solution to the reducing alcohol D is 1:2-1:4.
[0067] In step (c), the reducing alcohol D is selected to be one or a mixture of ethylene glycol, thioethanol, isopropanol, hydroxypropanol, and tert-butanol.
[0068] In step (d), the reaction container is selected to be glass or quartz.
[0069] Preferably, in step (d), the optimal reaction temperature ranges from 155 to 195° C., and the optimal reaction time ranges from 30 to 60 min.
[0070] The solvent used for washing in step (e) is methanol, dichloromethane or cyclohexane. Preferably, the solvent is a mixture of methanol and dichloromethane in a volume ratio of 1:3, and the washing is performed more than 3 times; the speed used in the centrifugation process is 4000-6000 rpm.
[0071] The particle diameter of the obtained nano Cu powder is 25-400nm, and the average particle diameter is 80nm; the surface of the nano Cu is evenly covered with a dense organic amine coating layer.
[0072] The following is an explanation with reference to specific embodiments and comparative examples.
[0073] Example 1
[0074] A method for preparing an antioxidant nano copper powder comprises the following steps:
[0075] Step (a), dissolving 0.01 mol of copper acetate in 50 ml of 9-octadeceneamine, and adding 0.01 mol of sodium hydroxide to prepare a precursor solution;
[0076] Step (b), dissolving 0.025 mol L-ascorbic acid in 50 ml 9-octadeceneamine, and stirring with magnetic force at 40-80° C. for 10-20 min, until the color changes to orange or reddish brown, and cooling to room temperature to form a reaction solution;
[0077] Step (c), mixing the precursor solution and the reaction solution in equal volumes, and then immediately adding the mixed solution into 120 ml of ethylene glycol, stirring evenly to obtain a reaction system;
[0078] Step (d), placing the reaction system in step (c) in a glass reaction container and heating it to 155-195° C. at a heating rate of 20-40° C. / min. In this step, the present embodiment adopts three different reaction temperatures for reaction in parallel, namely 155° C., 175° C., and 195° C., and keeps the temperature for 30 min. After cooling to room temperature, dark red products are obtained;
[0079] Step (e), washing, centrifuging and vacuum drying the dark red product to obtain nano copper powder, which is then sealed for later use. The washing solvent is a mixture of methanol and dichloromethane in a volume ratio of 1:3, and the washing is performed three times; the speed used in the centrifugal process is 4000-6000 rpm. The SEM / SE images of the obtained nano Cu powder are as follows: Figure 1 As shown, the XRD pattern is Figure 2 As shown (the XRD obtained at the three reaction temperatures are the same), the transmission electron microscope bright field (TEM-BF) image and the energy dispersive spectrometer (EDS) surface scanning element distribution map are shown in Figure 3 shown.
[0080] like Figure 1 to Figure 3 As shown in the figure, the particle diameter of the nano Cu powder obtained at different reaction temperatures is 120-400nm, and the nano Cu exhibits a polycrystalline structure. At the same time, the element distribution diagram of C and O elements shows that C and O elements show the same distribution trend, indicating that the surface of the nano Cu is not oxidized CuO, but because the Cu surface is evenly covered with a thin and dense organic amine coating layer ( Figure 5 bd). In addition Figure 2 It can also be seen from the XRD spectrum shown that the nano-Cu powder does not have any CuO diffraction peak, which once again proves that this method can obtain nano-Cu powder with extremely strong oxidation resistance.
[0081] The nano Cu powder prepared as above is further used to prepare a nano copper solder paste, and the steps are as follows: 0.9 parts of pine alcohol, 0.05 parts of ethyl cellulose and 0.05 parts of cellulose acetate are added to 9 parts of nano Cu powder, and the mixture is put into a mixing tank and stirred thoroughly at a stirring speed of 1800 r / s and a stirring time of 300 s to obtain a nano copper solder paste; the prepared solder paste is stored in a freezing environment of -5 to 0°C, and the solder paste needs to be thawed at room temperature for 1 to 2 hours before soldering the upper and lower chips.
[0082] The solder paste is evenly applied to the back of one or both sides of the chip by screen printing 2 to 3 times. The scraper is made of polyurethane, the screen is made of nylon, the thickness of the screen is 20 μm, the mesh size of the screen is 300 mesh, the distance from the screen to the chip surface is set to 0.6 mm before printing, the scraper movement speed is 0.5 cm / s, and the scraper angle is 5°.
[0083] Furthermore, after the first preheating (preheating temperature is 80°C, preheating time is 3 minutes), the upper and lower chips to be interconnected are placed relative to each other using a placement machine and a fixture. After the second preheating (preheating temperature is 60°C, preheating time is 6 minutes), vacuum hot pressing sintering is used to achieve mechanical and electrical interconnection of the upper and lower chips, wherein the vacuum degree is <5×10 - 2 MPa, the welding pressure applied to the chip is 10MPa, the sintering temperature is 250-300℃, and the sintering time is 30min.
[0084] This method regulates the long-chain amine coating effect by controlling the reaction temperature, and generates a uniform, dense and extremely thin small molecular weight organic amine coating layer on the surface of nano Cu powder, which reduces the particle size of nano Cu powder and significantly inhibits the oxidation of Cu. A matching screen printing process is designed, and a corresponding sintering process window is built, which effectively reduces the sintering temperature and time, and obtains interconnects with high printing accuracy (thickness 20μm), good oxidation resistance (no CuO diffraction peak) and high reliability interface. The shear strength of the interconnects after sintering can reach 36MPa, reaching the same level as the Sn-based solder commonly used in the market, and basically meets the needs of third-generation semiconductor packaging.
[0085] Example 2
[0086] A method for preparing an antioxidant nano copper powder, which is different from Example 1 in that:
[0087] In step (a), the copper salt is copper nitrate, and different amounts of sodium hydroxide are added to prepare a precursor solution; the molar ratio of the added sodium hydroxide to the copper salt is 0.5:1, 1:1, and 2:1, respectively, and a blank control group is set, that is, no sodium hydroxide is added.
[0088] In step (d), the heating temperature is increased to 175° C.;
[0089] The solvents used in step (a) and step (b) are N,N-dimethyldodecyl tertiary amine, and the reducing alcohol D in step (c) is tert-butyl alcohol.
[0090] The SEM / SE images of the Cu nanoparticles obtained in this example are as follows: Figure 4 As shown in FIG. 1 , it can be seen that the particle diameter of the nano Cu powder obtained by the method is 80 to 300 nm, especially when the molar mass ratio of sodium hydroxide to copper acetate is in the range of 1:1 to 2:1, the size of the nano Cu powder is smaller and the distribution is more uniform, and the average particle diameter can be as low as 140 nm (e.g. Figure 4 (c)-4(d)), the smaller nanosize can exert a stronger size effect and high surface energy advantage, achieving lower temperature sintering. At the same time, it can be seen that the Cu surface is evenly covered with an organic amine coating layer.
[0091] In this embodiment, the composition of the nano solder paste is: 1.4 parts of terpineol, 0.05 parts of ethyl cellulose and 0.05 parts of cellulose acetate are added to 8.5 parts of nano Cu powder. Further, the viscosity of the nano Cu paste in this solution is reduced, the mesh size of the screen is adjusted to 200 mesh, the distance from the screen to the chip surface is adjusted to 0.4mm before printing, the movement speed of the scraper is increased to 1cm / s, and the angle of the scraper is adjusted to 15°.
[0092] The sintering temperature in the vacuum hot pressing sintering step is 200-250° C., and the sintering time is 30 minutes.
[0093] This method controls the long-chain amine coating effect by controlling the concentration of alkali based on the optimal reaction temperature, further reducing the particle size of nano Cu powder. Smaller particle size, lower viscosity and suitable screen printing process can further reduce the sintering temperature to 200-250°C. The shear strength of the interconnected joint after sintering can reach 43MPa. The strength change during the shear test is shown in Figure 6 This strength exceeds the same level of Sn-based solder commonly used in the market and meets the requirements of third-generation semiconductor packaging.
[0094] Example 3
[0095] A method for preparing an antioxidant nano copper powder, which is different from Example 1 and Example 2 in that:
[0096] In step (a), the copper salt is copper chloride, and 0.01 mol of sodium hydroxide is added to prepare a precursor solution;
[0097] In step (d), the mixture is heated to 175° C. and kept warm for 15 to 120 minutes, and then cooled to room temperature to obtain a dark red product. In this embodiment, different holding times, i.e., reaction times, are set, namely (a) 15 minutes, (b) 30 minutes, (c) 60 minutes, and (d) 120 minutes.
[0098] The solvent used in step (a) and step (b) is N,N-dimethyldodecylamine, and the reducing alcohol D in step (c) is isopropanol.
[0099] SEM / SE images of Cu nanoparticles obtained at different reaction times are shown in Figure 2. Figure 5 As shown, it can be seen that the particle diameter of the nano Cu powder obtained in this embodiment is 20-240nm, especially when the reaction time is in the range of 30-60min, the size of the nano Cu powder is smaller and the distribution is more uniform, and the average particle diameter can be as low as 80nm ( Figure 5 (b)-5(c)), it is precisely because of such a small particle size that it is possible to achieve the preparation of ultra-high strength sintered joints at a lower subsequent sintering temperature.
[0100] The formula and steps of preparing solder paste using the nano Cu powder prepared in this embodiment are the same as those in embodiment 1. However, since the particle size is smaller than that in embodiment 1, the screen printing parameters are different:
[0101] The mesh size of the screen was 300 meshes. Before printing, the distance from the screen to the chip surface was set to 0.4 mm, the movement speed of the scraper was 1 cm / s, and the scraper angle was 10°.
[0102] In the vacuum hot pressing sintering step, the sintering temperature is 200-350° C. and the sintering time is 40 minutes.
[0103] In this embodiment, the long-chain amine coating effect is further regulated by controlling the reaction time. Figure 5 The SEM / SE images of the copper powder show that with the increase of reaction time, the particle size first decreases and then increases. When the reaction temperature is 30 min, the particle size is the smallest, and the average grain size is 90 nm. This scheme fully utilizes the characteristics of nano Cu powder, such as low cost, anti-electromigration, high surface energy and low temperature sintering, and still obtains interconnection joints with high printing accuracy, good anti-oxidation performance and high reliability interface. The shear strength of the interconnection joint after sintering can reach 48 MPa. Figure 6 As shown, its strength level far exceeds that of the Sn-based solder commonly used in the market, and fully meets the needs of third-generation semiconductor device packaging.
[0104] Comparative Example 1
[0105] On the basis of Examples 1 to 3, the reaction temperature of this comparative example is different, mainly:
[0106] The reaction temperature is 115 and 135°C (two different reaction temperatures). At a lower reaction temperature, the molecular movement speed of the reactants is slower, and the reaction energy cannot reach the energy required for nucleation, resulting in a slower nucleation rate. At the same time, the number of nuclei that can be formed is relatively small. In this case, the crystals formed will have a larger crystal size or even no corresponding crystals due to the lack of sufficient nuclei and the slower nucleation rate, which does not meet the requirements of nanoparticles required for low-temperature sintering of chips.
[0107] Comparison photos of the solutions after the reaction between Example 1 and Comparative Example 1 are as follows Figure 7 As shown, the reaction temperature is 135°C and 115°C and the final reaction solution is as follows Figure 7 b, 7c, the solution is still light yellow or white, that is, the Cu ions are not completely reduced or even not reduced at the low reaction temperature process. Figure 7As shown in a (the conditions of Examples 1 to 3 are the same, only the condition of 155° C. in Example 1 is listed for comparison), the solutions of Examples 1 to 3 after reacting at the appropriate reaction temperature are dark red, indicating that the increase in reaction temperature promotes the rapid formation and growth of crystal nuclei, thereby generating a large number of nano Cu particles, and the bottom of the centrifuge tube is the generated nano Cu powder.
[0108] Comparative Example 2
[0109] On the basis of Examples 1 to 3, the reaction time of this comparative example is different, mainly:
[0110] The reaction time was 150 min. Due to the long reaction time, a large number of nano Cu particles agglomerated together, and the morphology of the nano Cu powder finally obtained was as shown in the figure. Figure 8 As shown in the figure, the size of the formed nano Cu particles is large and irregular, and some particles reach the micrometer level. This greatly reduces the surface energy and the number of surface active sites of the particles. If the joint strength after sintering is to reach that in Examples 1 to 3, the sintering temperature, pressure and sintering time need to be significantly increased. In addition, if the reaction time is too long, large-area cross-linking of organic matter occurs, such as Figure 8 As shown in Figure 2, even after 4-5 times of methanol and dichloromethane mixed cleaning, the organic matter adhering to the particle surface cannot be removed, which also reduces the density and reliability of the sintered joint.
[0111] Comparative Example 3
[0112] Based on Examples 1 to 3, the cleaning solvent composition and times of this comparative example are different, mainly:
[0113] The cleaning solvents were water and ethanol, and the cleaning times were 3 times. The nano Cu powder obtained after 3 times of washing with water and ethanol was as follows: Fig. 9 As shown in (a), the cleaning effect is extremely unsatisfactory, and the nano Cu particles are wrapped by a large amount of residual organic matter and cannot be removed, which hinders the contact of the nano Cu in the subsequent sintering process. This is extremely unfavorable for subsequent reliable sintering.
[0114] The cleaning solvent is methanol and dichloromethane in a volume ratio of 1:2. The cleaning frequency is 1 time. The copper powder obtained is shown in the following figure. Fig. 9 As shown in (b), it can be seen that after cleaning once, the residual organic matter around the nano-Cu powder is significantly reduced.
[0115] In Example 1, the cleaning solvent is methanol and dichloromethane in a volume ratio of 1:3, and the cleaning times are 2 times. The obtained copper powder is shown in the figure below. Fig. 9 As shown in (c), it can be seen that after cleaning twice, there is almost no residual organic matter around the nano Cu powder particles.
[0116] It can be seen that the cleaning solvent of Example 1 is more efficient. However, the effect can also be achieved by cleaning several times with methanol and dichloromethane in a volume ratio of 1:2.
[0117] In summary, the technical solution of the present invention improves the preparation method of the traditional nano Cu powder, and controls the long-chain amine coating effect by controlling the reaction conditions (reaction temperature, alkali concentration and reaction time, etc.), and generates a uniform, dense and extremely thin small molecular weight organic amine coating layer on the surface of the nano Cu powder, which significantly reduces the particle size of the nano Cu powder (the average particle size can reach 80nm), and inhibits the oxidation of Cu during the synthesis process. On this basis, the solder paste components and screen printing process matching the nano Cu powder are designed, and the corresponding sintering process window is built, giving full play to the low cost, anti-electromigration, high surface energy and low temperature sintering characteristics of the nano Cu powder, especially effectively reducing the sintering temperature and time, and obtaining an interconnection joint with high printing accuracy (thickness 20μm), good anti-oxidation performance and high reliability interface, which meets the packaging needs of the third generation semiconductor devices.
[0118] Comparative Example 4
[0119] Based on Example 1, the difference of this comparative example is that the long-chain alkylamine is hexadecylamine which is not easy to volatilize at low temperature. In addition, when preparing the solder paste, only terpineol is used as the solder paste component, and the sintering process parameters are kept unchanged.
[0120] After sintering, the strength of the sintered joint of "chip-Cu nano solder paste layer-substrate" is less than 20MPa or even almost zero, and the strength is significantly reduced. Fig.10 As shown in the figure, it can be seen that the white area in the middle is the sintered Cu, and the surrounding black area is the residual organic matter and unsintered nanoparticles. Since the long-chain alkylamine in this scheme is not easy to volatilize, the organic amine coated on the Cu surface is not removed before sintering; since the solder paste flow effect provided by the single pine oil is poor, a large amount of organic matter remains around the nanoparticles. Both of these factors will hinder the formation of dense sintering structure between Cu and Cu nanoparticles, and cause large cracks at the interface, thereby significantly reducing the strength of the sintered joint. It also illustrates the importance of using ethyl cellulose and cellulose acetate in solder paste.
[0121] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A method for preparing an antioxidant nano copper powder, characterized in that: The steps include: Step S1, dissolving a copper salt in a solvent, adding a soluble metal hydroxide, and preparing a precursor solution; wherein the molar ratio of the soluble metal hydroxide to the copper salt is 0.5-2:1; Step S2, dissolving L-ascorbic acid in a solvent, stirring at 40-80° C. for 10-20 min, waiting for the color to change to orange or reddish brown, and cooling to room temperature to obtain a reaction solution; Step S3, mixing the precursor solution and the reaction solution to obtain a mixed solution, wherein the molar ratio of copper salt to L-ascorbic acid is 1:2-4; adding the mixed solution to the reducing alcohol, stirring evenly, heating to a reaction temperature of 155-195° C., and keeping the temperature for reaction for more than 15 minutes, and cooling to room temperature to obtain a product; Step S4, washing, centrifuging and drying the product to obtain antioxidant nano copper powder; The solvent in step S1 and step S2 is one or a mixture of two or more of 9-octadeceneamine, N,N-dimethyldodecyl tertiary amine, N,N-dimethyldodecylamine and N,N-diethyltrimethylsilylamine.
2. The method for preparing the antioxidant nano copper powder according to claim 1, characterized in that: The copper salt is one of copper sulfate, copper chloride, copper nitrate and copper acetate, or a mixture of two or more thereof.
3. The method for preparing the antioxidant nano copper powder according to claim 2, characterized in that: In the precursor solution, the concentration of copper salt is 0.1-1 mol / L, and the molar ratio of the soluble metal hydroxide to the copper salt is 1-2:1; in the reaction solution, the concentration of L-ascorbic acid is 0.4-2 mol / L; in step S3, the precursor solution and the reaction solution are mixed in equal volumes, and the volume ratio of the mixed solution to the reducing alcohol is 1:2-1:
4.
4. The method for preparing the antioxidant nano copper powder according to claim 3, characterized in that: The reducing alcohol is one or a mixture of two or more of ethylene glycol, thioethanol, isopropanol, hydroxypropanol and tert-butanol.
5. The method for preparing the antioxidant nano copper powder according to claim 1, characterized in that: In step S3, the reaction time is 30 to 60 minutes; in step S4, the washing solvent is methanol, dichloromethane or cyclohexane; the centrifugal washing is performed more than three times, and the centrifugal speed is 4000 to 6000 rpm; the particle diameter of the antioxidant nano copper powder is 25 to 400 nm.
6. An antioxidant nano copper powder, characterized in that: The anti-oxidation nano copper powder is prepared by the method for preparing the anti-oxidation nano copper powder according to any one of claims 1 to 5, and the surface of the anti-oxidation nano copper powder is covered with an organic amine coating layer.
7. A nano copper solder paste, characterized in that: The anti-oxidation nano copper powder as claimed in claim 6 is uniformly mixed with a solvent and a soldering flux; the mass ratio of the anti-oxidation nano copper powder, the solvent and the soldering flux is (7-9):(1-3):(0.02-0.06).
8. The nano copper solder paste according to claim 7, characterized in that: The solvent is pineol, and the soldering flux contains ethyl cellulose and cellulose acetate; the stirring speed is 1800-2200 r / s, and the stirring time is 180-300 s.
9. A method for low temperature sintering interconnection of components, characterized in that: The nano copper solder paste described in claim 7 is applied to the surface of the components to be welded, and after preheating, vacuum hot pressing and sintering are performed.
10. The method for interconnecting components by low temperature sintering according to claim 9, characterized in that: The nano copper solder paste is evenly applied to the surface to be connected of the components by screen printing 2 to 3 times, the components are placed at the position to be connected after the first preheating, and after the second preheating, vacuum hot pressing sintering is used to achieve interconnection; The screen printing adopts a screen thickness of 20-50 μm, a mesh size of 200-300 meshes, a distance between the screen and the chip surface is set to 0.4-0.6 mm before printing, a scraper movement speed of 0.5-1 cm / s, and a scraper angle of 5-15°; the first preheating temperature is 80-100°C, and the preheating time is 2-3 min; the second preheating temperature is 60-80°C, and the preheating time is 5-6 min; The vacuum degree of the vacuum hot pressing sintering is less than 5×10 -2 MPa, the pressure is 5-15MPa, and the sintering temperature is 200-350℃.
Citation Information
Patent Citations
Preparation method of copper nano-particle soldering paste and product thereof
CN108098191A
Green and environment-friendly conductive nano-copper ink and preparation method thereof
CN111496266A
High-temperature-resistant and high-humidity-resistant nano-copper and preparation method thereof
CN118720129A
Oxidation resistant copper nanoparticles and method for producing same
US20150344715A1